Influence of perioperative stress on central and peripheral oxytocin and arginine‐vasopressin concentrations. (14th October 2019) - Kagerbauer, Simone Maria; Martin, Jan; Ulm, Bernhard; Jungwirth, Bettina; Podtschaske, Armin Horst
Abstract: Perioperative stress provides not only physical, but also psychic and emotional aspects, which may influence the hypothalamic neuropeptide system. Studies investigating the perioperative course of central neuropeptide activity are missing. Therefore, the present study aimed to determine perioperative fluctuations in central and concomitant peripheral concentrations of the hypothalamic neuropeptides oxytocin (OXT) and arginine‐vasopressin (AVP), as well as their impact on perioperative anxiety and depression. Cerebrospinal fluid (CSF), blood and saliva were collected from 12 patients who underwent elective endovascular aortic repair with a routinely inserted spinal catheter. AVP and OXT concentrations were analysed at four timepoints: (i) the evening before the operation; (ii) the operation day immediately before anaesthesia induction; (iii) intraoperatively after the stent was placed; and (iv) on day 1 after the operation. Patients completed the Hospital Anxiety and Depression Scale (HADS) at timepoints 1 and 4. For CSF OXT, the present study showed a significant intraoperative decline, accompanied by a decrease in saliva. OXT blood concentrations before anaesthesia induction were higher than at the evening before the operation. OXT concentrations in CSF and saliva correlated well at timepoints 2‐4. AVP concentrations in CSF, blood and saliva did not show any significant changes perioperatively. However, postoperative AVP blood concentrations showed a significant negative correlation with anxiety and depression scores according to the HADS. This pilot study demonstrates perioperative fluctuations in central OXT concentrations, which are better reflected by saliva than by blood. Further studies are required to determine whether OXT and AVP can predict postoperative post‐traumatic stress disorder.